DINAMIKA POPULASI ATACTODEA STRIATA (GMELIN, 1791) (MOLLUSCA: MESODESMATIDAE) DI PANTAI BERPASIR OHOIDER, KEP. KEI KECIL, MALUKU TENGGARA - Heryanto, Heryanto; Radjab, A.W. (JURNAL BIOLOGI INDONESIA, 2014)
Atactodea striata (Gmelin, 1791) are inhabitants of the sandy at Village Ohoider, Kei Kecil Islands, MalukuTenggara. Sampling has been carried out on the 15th of September 1997 to October 1998 for the shell heightmeasurement. Monthly length frequency data were then analyzed using the software FiSAT II to estimatepopulation parameters such as population structure, age maximum, maximum length, growth and recruitment.Result obtained from this study is that Atactodea striata shells generally consist of four age groups, except in certainmonths were widened to five because of the occurence of old shell group. Mussels in this study reproducemultivoltine with expected life span of almost four years. The maximum length of the mussels is 19.03 mm at 95%confidence level, and the growth coefficient K = 0.37 with a growth performance index Ï? '= 1.74. Observations onhabitat sediment discovered that these shells prefer to live in the fine sand with range of fire grain of 65.96 to69.09%.Keywords:: Dynamics Population, Atactodea striata, Kei Kecil Islands, Maluku Tenggara